From Scholarly Knowledge to Knowledge to be Taught: The Case of Vector Introduction (Journal of Didactic Studies, 2023)
The incorporation of the contextualization and tangible instances in the diffusion of vector concepts in a textbook can lead to students forming a concept image that differs from the scientific understanding due to their perceptions and actions towards the learning environment. This study aims to expose potential learning obstacles in vector introduction caused by external didactic transposition through the study of textbook analysis. Meta-discourse served as the methodological analysis. Two textbooks were analyzed based on concept declaration, the changing environment, and didactic phenomena. Based on the concept declaration, the presence of an epistemological obstacle is a potential learning barrier. Additionally, changes in the learning environment can contribute to ontogenic obstacles. In conclusion, the analysis of the three textbooks reveals that potential learning obstacles encompass both ontogenic and epistemological aspects.